Spirituality as a potential essence of creative personality growth [Духовность как потенциальная сущность креативного роста личности] (in Russian) - Іванченко, Андреянна Олексіївна; Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна (My University, 2010)
In this paper a close mutual connection between the spirituality and creativity has been determined. It has been shown that the spiritual and energetic potential of the teacher has an influence in the straight and directly proportional way upon the creative and integral processes in the small educational group. В статье установлена тесная взаимовлияющая связь духовности и креативности. Показано, что на креативно-интегративные процессы в малой учебной группе непосредственное прямопропорциональное вляние оказывает духовный и энергетический потенциал преподавателя.
Keywords: духовність; креативність; духовний ріст